The Role of International Energy Agreements in Price Band Formation - OKHRIMENKO, Oksana; SAMSIN, Ihor; ZUBKO, Tetiana; LYTVYNENKO, Elena; KIIAKH, Ihor (Theoretical and Practical Research in Economic Fields, 2025)
The price of energy is one of the key determinants of the well-being of numerous countries, therefore, analysis of the factors of influence on such price formation is of great importance. This work aims at the determination of the main vectors of influence of international energy agreements on the formation of the price bands on the example of the Organization of the Petroleum Exporting Countries. Statistical analysis method, descriptive method, and correlation analysis method were used in the study. As a result of the study, the significant role of international energy agreements in the formation of the price bands was proved. Using the characteristic of the mechanism of influence of oil exporters on the prices of oil, the control major oil exporters can have over price formation. The analysis of price fluctuations in time enabled combining these fluctuations with key geopolitics and economic events of the relevant period, as well as explaining the influence of oil exporters on the price change. The offer of the members of the Organization of the Petroleum Exporting Countries significantly affects the prices of crude oil, spot prices, and prices of products, which was confirmed using correlation analysis. The influence of exporters is larger than that of the states outside the organization. Gasoline, Diesel, and Jet/Kero are the most sensitive to fluctuations in the offer of the Organization of the Petroleum Exporting Countries. Not only official energy agreements but also informal practices significantly influence the formation of price bands, which was demonstrated through the analysis of the revenue from Russian oil exports. Governments and energy companies may use these results for optimisation of strategies for managing risks associated with the actions of international organizations.